Beyond magenta : transgender teens speak out - Kuklin, Susan, frey50 (Somerville, Massachusetts Candlewick Press, 2014)
A groundbreaking work of LGBT literature takes an honest look at the life, love, and struggles of transgender teens. Author and photographer Susan Kuklin met and interviewed six transgender or gender-neutral young adults and used her considerable skills to represent them thoughtfully and respectfully before, during, and after their personal acknowledgment of gender preference. Portraits, family photographs, and candid images grace the pages, augmenting the emotional and physical journey each youth has taken. Each honest discussion and disclosure, whether joyful or heartbreaking, is completely different from the other because of family dynamics, living situations, gender, and the transition these teens make in recognition of their true selves.
Spectrum. Jessy: the house of my soul ; Christina: every girl is different ; Mariah: the real deal ; Cameron: variables ; Nat: something else -- Lifeline. Luke: untouchable -- Notes and resources. Author's note ; About the Callen-Lorde community health center ; Q&A with Dr. Manel Silva ; About Proud Theater.
Keywords: Transgenderism; Transgender youth; Gender identity